Pertumbuhan dan Perkembangan Jiwa Beragama pada Anak Kelas 3 di SD Az-Zakiyah Islamic Leadership - Diva Adriana Simatupang; Wirda Indri Khairizka; Ramadan Lubis; Alya Rina Armalia Pane; Irma Hidayah Batubara; Zikri Ablia (Jurnal Bintang Pendidikan Indonesia, 2024)
Religious development in childhood occurs through life experiences during childhood itself, which occur in the family, at school, and in the surrounding community. The more religious experience there is (in accordance with religious teachings) and the more religious elements there are, the more attitudes, actions, behavior and ways of dealing with life will be in accordance with religious teachings. This research aims to increase the growth and development of the religious spirit to a more concrete level in grade 3 children at Az-Zakiyah Islamic Leadership Elementary School, Medan. The research method used is a descriptive qualitative research method with data collection through interviews, analysis, direct activities and documentation. The research subjects were 17 students, with a composition of 10 women and 7 men. The results of this research discussion show that the development of the religious spirit in children goes through 3 different stages.